Analysis of Cadmium Contamination in Well Water Around the Terjun Landfill Medan Marelan District - Muhammad Syafii; Taufik Ashar; Nurmaini Nurmaini (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The increase in waste volume significantly affects the waste generation at Landfills. Landfills have been identified as one of the main groundwater pollution sources. The aim of this study was to determine the factors influencing cadmium pollution in well water among the community around the Terjun Landfill Medan Marelan District. This study employed an observational analytic design with a cross-sectional approach. It was conducted in the Medan Marelan District adjacent to the Terjun Landfill from August to November 2023. The study population consisted of all households with wells, totaling 218 households. Sample size calculation yielded 64 samples. Sampling technique was conducted using simple random sampling. Sample collection is based on the direction of water flow. Well water samples were examined in the laboratory using spectrophotometry by the Environmental Health and Disease Control Technical Implementation Class I Medan Unit on October 11, 2023, and the results were received on October 30, 2023. Data analysis using SPSS version 21. Data analysis involved three stages: univariate analysis using descriptive statistics and frequency, bivariate analysis using Pearson and ANOVA tests, and multivariate analysis using multiple linear regression at a significance level of 95% (0.05). Statistics results the relationship between well distance and cadmium levels with a value of (P=0.001;r=-0.676), indicating a significant relationship. The relationship between well depth and cadmium levels yielded a value of (P=0.001;r=0.612), indicating a significant relationship. Cadmium levels with soil types obtained a value of (P=0.001), indicating a significant difference. The factor most influencing cadmium pollution in well water around the Terjun Landfill was well distance (ExpB=0.002;P=0.001). The average cadmium levels in well water are still below the drinking water quality standards, however continuous consumption poses risks. The most influential factor is well distance. It is recommended that residents refrain from using well water as a drinking water source. Keywords : Cadmium, landfill, Well Water